$c$-$(τ_1,τ_2)$-continuity for Multifunctions (European Journal of Pure and Applied Mathematics, 2024)
This paper is concerned with the concepts of upper and lower $c$-$(τ_1,τ_2)$-continuous multifunctions. Moreover, several characterizations of upper and lower $c$-$(τ_1,τ_2)$-continuous multifunctions are investigated.
Keywords: upper $c$-$(τ_1,τ_2)$-continuous multifunction; lower $c$-$(τ_1,τ_2)$-continuous multifunction